Damage and fracture behavior and spatio-temporal evolution of acoustic emission of sandstone before and after laser radiation - Gao, Ming-zhong; Liu, Jun-jun; Li, Chun-xiang; Yang, Ben-gao; Li, Fei; Zhou, Xue-min; Yang, Lei; Yang, Zun-dong; Xie, Jing (Journal of Central South University, 2024)
Laser technology holds significant promise for enhancing rock-breaking efficiency. Experimental investigations were carried out on sandstone subjected to laser radiation, aiming to elucidate its response mechanism to such radiation. The uniaxial compressive strength of sandstone notably decreases by 22.1%–54.7% following exposure to a 750 W laser for 30 s, indicating a substantial weakening effect. Furthermore, the elastic modulus and Poisson ratio of sandstone exhibit an average decrease of 33.7% and 25.9%, respectively. Simultaneously, laser radiation reduces the brittleness of sandstone, increases the dissipated energy proportion, and shifts the failure mode from tensile to tension-shear composite failure. Following laser radiation, both the number and energy of acoustic emission events in the sandstone register a substantial increase, with a more dispersed distribution of these events. In summary, laser radiation induces notable damage to the mechanical properties of sandstone, leading to a substantial decrease in elastic energy storage capacity. Laser rock breaking technology is expected to be applied in hard rock breaking engineering to significantly reduce the difficulty of rock breaking and improve rock breaking efficiency.